Longitudinal Investigation of Older Adults' Ability to Self‐Manage Complex Drug Regimens. Issue 3 (25th November 2019) - Bailey, Stacy Cooper; Opsasnick, Lauren A.; Curtis, Laura M.; Federman, Alex D.; Benavente, Julia Y.; O'Conor, Rachel; Wolf, Michael S.
Abstract : OBJECTIVES: We sought to investigate older patients' ability to correctly and efficiently dose multidrug regimens over nearly a decade and to explore factors predicting declines in medication self‐management. DESIGN: Longitudinal cohort study funded by the National Institute on Aging. SETTING: One academic internal medicine clinic and six community health centers. PARTICIPANTS: Beginning in 2008, 900 English‐speaking adults, aged 55 to 74 years, were enrolled in the study, completing a baseline (T1) assessment. To date, 303 participants have completed the same assessment 9 years postbaseline (T4). MEASUREMENTS: At T1, subjects were given a standardized, seven‐drug regimen and asked to demonstrate how they would take medicine over 24 hours. The number of dosing errors made and times per day that a participant would take medicine were recorded. Health literacy was measured via the Newest Vital Sign, and cognitive decline was measured by the Mini‐Mental State Examination. RESULTS: Participants on average made 2.9 dosing errors (SD = 2.5 dosing errors; range = 0‐21 dosing errors) of 21 potential errors at T1 and 5.0 errors (SD = 2.1 errors; range = 1‐18 errors; P  < .001) at T4. In a multivariate model, limited literacy (β = .69; 95% confidence interval [CI] = .18‐1.20; P = .01), meaningful cognitive decline (β = 1.72; 95% CI = .70‐2.74; P = .01), number of chronic conditions (β = .21; 95% CI = .07‐.34; P = .01), and number of baseline dosing errors (β = −.76; 95% CI = −.85 to −.67; P  < .001) were significant, independent predictors of changes in dosing errors. Most patients overcomplicated their daily medication schedule; no sociodemographic characteristics were predictive of poor regimen organization in multivariate models. In a multivariate model, there were no significant predictors of changes in regimen consolidation over time, except regimen consolidation at T1. CONCLUSIONS: Older patients frequently overcomplicated drug regimens and increasingly made more dosing errors over 9 years of follow‐up. Patients with limited literacy, cognitive decline, and multimorbidity were at greatest risk for errors. J Am Geriatr Soc 68:569–575, 2020